Evaluating tsunami evacuation routes and shelter capacity using GIS and travel time analysis in Aceh Besar, Indonesia - cut mutiawati; Miswar Tarihoran; Juliana Fisaini (International Journal of Disaster Management, 2025)
Tsunamis remain a major hazard for coastal populations, particularly in tectonically active zones such as Indonesia. Strategic evacuation planning plays a critical role in minimizing disaster impacts and improving local resilience. This research focuses on identifying appropriate Temporary Evacuation Stations (TES), Final Evacuation Stations (FES), and accessible evacuation routes within Aceh Besar Regency, utilizing road geometry and estimated travel time as key criteria. Geospatial datasetsincluding road networks, facility locations, and elevation profileswere processed using Geographic Information System (GIS) analysis and tsunami inundation modeling. The analysis shows that Neuheun Village contains five TES and four FES, Lamnga hosts one TES, while Baro lacks suitable evacuation infrastructure. Many routes in the study area fall short of standard requirements for width and travel time, especially for pedestrians. Existing TES buildings can accommodate only about 34.52% of the total population. Although motorbikes serve as practical evacuation options, the narrowness of roads limits the use of cars. These findings emphasize the pressing need for additional vertical evacuation shelters and enhancements to road networks to support effective tsunami response strategies.